2006
DOI: 10.1117/12.655541
|View full text |Cite
|
Sign up to set email alerts
|

Immersion topcoat and resist material improvement study by using immersion scanner

Abstract: ArF (193nm) immersion lithography is considered as the most promising next generation technology and significant effort to establish the immersion process for semiconductor device HVM is currently focused on the tool, material and process development. Immersion lithography enables the design of hyper numerical aperture (NA>1) lens systems by filling the gap between lens and resist with an immersion medium. Water is the ideal medium for 193nm immersion lithography and the water immersion system could reach up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Many researchers have attempted to correlate immersion defectivity with some easily measured property of topcoat materials. In general, defectivity has found to decrease with increasing SRCA. ,,,, For example, Nikon showed that defectivity was markedly reduced with topcoats having receding water contact angles near 70° (Figure ) . This transition from high to low defectivity occurs above the critical velocity for film pulling (∼50°−60°) discussed previously .…”
Section: Materials For 193 Nm Water Immersion Lithographymentioning
confidence: 97%
See 1 more Smart Citation
“…Many researchers have attempted to correlate immersion defectivity with some easily measured property of topcoat materials. In general, defectivity has found to decrease with increasing SRCA. ,,,, For example, Nikon showed that defectivity was markedly reduced with topcoats having receding water contact angles near 70° (Figure ) . This transition from high to low defectivity occurs above the critical velocity for film pulling (∼50°−60°) discussed previously .…”
Section: Materials For 193 Nm Water Immersion Lithographymentioning
confidence: 97%
“…Many experimental techniques have been devised to measure the kinetics of resist component extraction by water in order to meet these specifications. These techniques include simple contact of the resist surface to water confined in an O-ring or vial, flowing water through a specifically designed cell mounted on the wafer, or dragging a drop or puddle of fluid across the resist-coated wafer. ,,, In an attempt to standardize leaching measurements, many vendors now utilize a dynamic method employing a multichannel flow cell (so-called dynamic WEXA)…”
Section: Materials For 193 Nm Water Immersion Lithographymentioning
confidence: 99%
“…Application of these topcoats could make most of dry-photoresist usable in immersion process. Additionally, good scanning property of topcoat led to fewer defects because of fewer remaining water droplets 12 . In order to suppress watermark defect completely, preventing water penetration into topcoat film is important as well.…”
mentioning
confidence: 99%